The use of a geographic information system (GIS) for farm soil conservation planning : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Soil Science at Massey University - Priyono, Cyprianus Nugroho Sulistyo (Massey University, 1993)
The use of a Geographic Information Systems (PC ARC/INFO) for farm soil conservation planning was demonstrated in several neighbouring properties in the Apiti district, Manawatu. The area (775 ha) was mainly steep and strongly rolling hill country where the dominant land use was pastoral grazing by sheep and cattle. The main objective of this study was to utilize the GIS at each step of the farm soil conservation planning process. The planning process began with a land resources inventory (LRI) where information on basic physical resources relevant to land management and soil conservation was collected and stored in a database before further processing. Factors collected in the LRI included primary factors (soil type, soil depth, slope, rock type and elevation) and secondary factors (existing erosion, land use, fence lines and ownership, and drainage condition). A digital elevation model (DEM) was developed to display landforms. Field observations were also used and local farmers were given the opportunity to become involved in the planning process. The next step involved delineating areas of similar land use capability and potential land use. The areas were also assessed in terms of potential erosion and conservation needs. These operations were undertaken by combining the LRI factors in various ways. Results of these assessments were matched to define land units which have similar physical characteristics. Recommendations for management practices were then made by considering combinations of the factors. The plan was displayed as maps showing the management options available for farmers. Both map overlay procedures and database analyses were carried out at each step of the planning process. As the map overlay is a unique operation in the GIS, it was used to combine necessary factors from the LRI based on a set of criteria. Database analyses were then carried out using macro commands which were developed according to the criteria. The ability of the GIS for database analyses distinguishes the GIS from other systems whose primary objective is map production. The use of database analyses in this study was a particular example for making recommendations in soil conservation planning. However, the techniques are applicable to many different conditions and different purposes. The maps presented in this study are examples of how it is possible to show the results of analyses. Advantages and constraints of such procedures at each step of the planning process were discussed.
Keywords: Rural land use; Soil conservation; Geographic information systems; Remote sensing; Planning